Patterns of local and nonlocal water resource use across the western U.S. determined via stable isotope intercomparisons. Issue 10 (16th October 2014) - Good, Stephen P.; Kennedy, Casey D.; Stalker, Jeremy C.; Chesson, Lesley A.; Valenzuela, Luciano O.; Beasley, Melanie M.; Ehleringer, James R.; Bowen, Gabriel. J.
Abstract In the western U.S., the mismatch between public water demands and natural water availability necessitates large interbasin transfers of water as well as groundwater mining of fossil aquifers. Here we identify probable situations of nonlocal water use in both space and time based on isotopic comparisons between tap waters and potential water resources within hydrologic basins. Our approach, which considers evaporative enrichment of heavy isotopes during storage and distribution, is used to determine the likelihood of local origin for 612 tap water samples collected from across the western U.S. We find that 64% of samples are isotopically distinct from precipitation falling within the local hydrologic basin, a proxy for groundwater with modern recharge, and 31% of samples are isotopically distinct from estimated surface water found within the local basin. Those samples inconsistent with local water sources, which we suggest are likely derived from water imported from other basins or extracted from fossil aquifers, are primarily clustered in southern California, the San Francisco Bay area, and central Arizona. Our isotope‐based estimates of nonlocal water use are correlated with both hydrogeomorphic and socioeconomic properties of basins, suggesting that these factors exert a predictable influence on the likelihood that nonlocal waters are used to supply tap water. We use these basin properties to develop a regional model of nonlocal water resource use that predicts (r2 = 0.64) isotopically inferred patterns and allows assessment of total interbasin transfer and/or fossil aquifer extraction volumes across the western U.S.